Konsep Infrastruktur Jalan Kota Timika Sebagai Kota Modern Timika City Road Infrastructure Concept as a Modern City - Kiwak, panius (Universitas Sulawesi Barat, 2023)
Abstract. This research was carried out on the axis of the district cross road, namely Luwu Regency and North Toraja Regency, namely the Batusitanduk-Sa'dan-Rantepao road axis. Where this location is an area that is very prone to landslides so this study aims to conduct studies related to how disaster mitigation forms must be carried out. The research method that will be used in this paper, which is descriptive, aims to describe the state/symptoms of a particular group and describe a certain relationship between a symptom and other symptoms. Sources and types in collecting data, namely using secondary data sources obtained from journals and news portals. The data analysis technique used by the author is descriptive qualitative analysis. The forms of disaster mitigation that can be carried out at the research location are physical mitigation, non-physical mitigation and social mitigation. As well as public awareness, especially increased vigilance during the rainy season with high intensity, is needed. Determining the right evacuation route also affects the process of saving residents in the event of a landslide. KEYWORD: Modern City, Smart City Infrastructure City, Infrastructure Road.